Democracy rising - Munoz, Heraldo (ed.) (New Delhi, 2007)
This timely assessment of both the progress toward democratic governance globally and the significant challenges that democracies face is the outcome of a workshop organized by the Community of Democracies. The Community is a group of more than a hundred countries devoted to the spread and consolidation of democracy around the world.
Keywords: Democracy